2004
DOI: 10.1073/pnas.0400005101
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of Bcl-2 protein family member Bim by T cell receptor triggering

Abstract: Bim, a proapoptotic BH3-only member of the Bcl-2 protein family, is required for central and peripheral deletion of T lymphocytes. Mechanisms regulating Bim activity in T cells remain poorly understood. We show that expression of Bim is up-regulated in human T cells after polyclonal or specific T cell receptor triggering. Induction of Bim was affected by the agonistic potency of MH-C:peptide ligands. Peptides that failed to induce Bim expression, failed to induce apoptosis in specific T cells, whereas partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
3
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 44 publications
5
57
3
1
Order By: Relevance
“…10 Our own studies using human CD8 ϩ T-cell blasts have shown that apoptosis by cytokine deprivation predominates over death receptor ligation and that high levels of Bim expression are necessary for this process to occur. 13 The expression of Bim and Bcl-x S clearly increases during the process of T-cell blast generation, 13,18,52 arriving at maximum levels around day 5 or 6 of stimulation, just at the point where human T-cell blasts begin to be sensitive to apoptosis and AICD. 8,53 Once the concentration of stimulatory cytokines decreases, prosurvival signals diminish and the levels of Bcl-2, Bcl-x L , and Mcl-1 rapidly decrease, whereas the levels of Bim expression are maintained high.…”
Section: Discussionmentioning
confidence: 99%
“…10 Our own studies using human CD8 ϩ T-cell blasts have shown that apoptosis by cytokine deprivation predominates over death receptor ligation and that high levels of Bim expression are necessary for this process to occur. 13 The expression of Bim and Bcl-x S clearly increases during the process of T-cell blast generation, 13,18,52 arriving at maximum levels around day 5 or 6 of stimulation, just at the point where human T-cell blasts begin to be sensitive to apoptosis and AICD. 8,53 Once the concentration of stimulatory cytokines decreases, prosurvival signals diminish and the levels of Bcl-2, Bcl-x L , and Mcl-1 rapidly decrease, whereas the levels of Bim expression are maintained high.…”
Section: Discussionmentioning
confidence: 99%
“…Bim, a pro-apoptotic member of the Bcl-2-family, is a candidate mediator of caspase-independent T cell death (67). Bim-deficient activated T cells are resistant to PCD (31), and Bim has been implicated in both AICD (68) and ACAD (69). Recent data indicate that Bim is crucial for the contraction of herpes simplex virus-specific CD8 ϩ T cells (70).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, cells from blood, lymph nodes, or spleens of LCMV-infected or naive mice were isolated as described above, then were incubated in round-bottom 96-well plates at 37°C, 5% CO 2 , for 5-7 h in the presence or absence of peptide in RPMI 1640 (containing 5-10% FBS, 100 M 2-ME, L-glutamine, and antibiotics). The peptides, used at a final concentration of 1-2 g/ml, represent dominant and subdominant CD8 ϩ T cell epitopes from LCMV: NP 118 [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] and NP 309 -328 (both H-2A b ). Brefeldin A (Sigma) was added to a final concentration of 5 g/ml.…”
Section: Intracellular Cytokine Staining (Iccs)mentioning
confidence: 99%
“…Bax -/-Bak -/-T cells are highly resistant to multiple cell death stimuli including cytokine deprivation [36]. Furthermore, in human T cells, Bim expression can be induced by TCR signaling [199]. Bim-deficient T cells are resistant to cytokine deprivation [134] and are defective in the CD8 + contraction phase in herpes simplex virus infection [200,201].…”
Section: Contraction Phase Of Cd8 + T Cell Immune Responsementioning
confidence: 99%